A Public Health Economic Assessment of Hospitals' Cost to Screen Newborns for Critical Congenital Heart Disease. (January 2014) - Peterson, Cora; Grosse, Scott D.; Glidewell, Jill; Garg, Lorraine F.; Braun, Kim Van Naarden; Knapp, Mary M.; Beres, Leslie M.; Hinton, Cynthia F.; Olney, Richard S.; Cassell, Cynthia H.
Objective: Critical congenital heart disease (CCHD) was recently added to the U.S. Recommended Uniform Screening Panel for newborns. This evaluation aimed to estimate screening time and hospital cost per newborn screened for CCHD using pulse oximetry as part of a public health economic assessment of CCHD screening. Methods: A cost survey and time and motion study were conducted in well-newborn and special/intensive care nurseries in a random sample of seven birthing hospitals in New Jersey, where the state legislature mandated CCHD screening in 2011. The sample was stratified by hospital facility level, hospital birth census, and geographic location. At the time of the evaluation, all hospitals had conducted CCHD screening for at least four months. Results: Mean screening time per newborn was 9.1 (standard deviation = 3.4) minutes. Hospitals' total mean estimated cost per newborn screened was 14.19 (in 2011 U.S. dollars), consisting of 7.36 in labor costs and 6.83 in equipment and supply costs. Conclusions: This federal agency-state health department collaborative assessment is the first state-level analysis of time and hospital costs for CCHD screening using pulse oximetry conducted in the U.S. Hospitals' cost per newborn screened for CCHD with pulse oximetry is comparable with cost estimates of existing newborn screening tests. Hospitals' equipment costs varied substantially based on the pulse oximetry technology employed, with lower costs among hospitals that used reusable screening sensors. In combination with estimates of screening accuracy, effectiveness, and avoided costs, information from this evaluation suggests that CCHD screening is cost-effective.